The two faces of auditory masking - JORASZ, U.; MOORE, B.C. J. (Archives of Acoustics, 2000)
The experiments are concerned with the comodulation masking release (CMR) and modulation discrimination interference (MDI) that can occur when modulated carriers are added to a target modulated sound at frequencies remote from the target frequency. The results are discussed in terms of the factors influencing the both effects.